2016
DOI: 10.14744/nci.2015.97269
|View full text |Cite
|
Sign up to set email alerts
|

An overview of Ebola virus disease

Abstract: Ebola virus disease (EVD), formerly known as Ebola hemorrhagic fever, is a severe, often fatal illness in humans. Ebola virus (EBOV) is transmitted through contact with blood or body fluids of a person who contracted or died from EVD, contaminated objects like needles and infected animals or bush meat. EVD has an incubation period of 2 to 21 days, and the infection has an acute onset without any carrier status. Currently, there is no standard treatment for EVD, so it is important to avoid infection or further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 18 publications
0
25
0
2
Order By: Relevance
“…A detailed assessment of content in this cohort revealed that 2 reports were merely focusing on West Nile virus without presenting data on phleboviruses and were subsequently omitted . Review articles that present general or agent‐specific information on vector‐borne infections in Turkey including phleboviruses comprised 7 of the entries, and they were examined for further cited research on phleboviruses. Two reports presented surveillance data on the mosquito‐borne pathogenic phlebovirus Rift Valley fever virus, where serological and nucleic acid tests gave negative results in 350 sera (from cattle, horse, sheep, goat, and water buffaloes) and in aborted fetuses, collected from the Black Sea region of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed assessment of content in this cohort revealed that 2 reports were merely focusing on West Nile virus without presenting data on phleboviruses and were subsequently omitted . Review articles that present general or agent‐specific information on vector‐borne infections in Turkey including phleboviruses comprised 7 of the entries, and they were examined for further cited research on phleboviruses. Two reports presented surveillance data on the mosquito‐borne pathogenic phlebovirus Rift Valley fever virus, where serological and nucleic acid tests gave negative results in 350 sera (from cattle, horse, sheep, goat, and water buffaloes) and in aborted fetuses, collected from the Black Sea region of Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Çünkü başlangıç bulguları spesifik değildir ve genellikle sıtma, tifo, menejit, sigelloz ve leptospiroz gibi hastalıklarla karışabilir (24,27,28) .…”
Section: Evhunclassified
“…Bu antikorlar bitkilerden özellikle nicotiana benthamianadan üretilir. Primatlar üzerinde kısıtlı sayıda yapılan çalışmalarda koruyucu etkisi saptanmıştır (28,29) .…”
Section: Tedaviunclassified
“…Ebola virus is belonging to Filoviruses Filoviridae family which is zoonotic pathogen that causes hemorrhagic fever for both human and nonhuman primate with high rate of death that exceeded 80% [1][2][3][4][5][6][7][8]. The first appearance of Ebola virus in Sudan, Yambuku, Nzara and Democratic Republic of Congo was in 1976 than it spread into a village near the Ebola River [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…The first appearance of Ebola virus in Sudan, Yambuku, Nzara and Democratic Republic of Congo was in 1976 than it spread into a village near the Ebola River [2,4].…”
Section: Introductionmentioning
confidence: 99%